An Evaluation of environmental sustainability performance via attitudes , social responsibility, and culture: a mediated analysis - Ajibike, W.A.; Adeleke, A. Q.; Fazeeda, Mohamad; Bamgbade, J.A.; M.N., M. Nawi; Moshood, T. D (Elsevier, 2021)
Demands for environmentally sustainable construction are driving firms towards the adoption of environmental sustainability practices, and the rising regulatory burden to reduce impacts on the intending users and other stakeholders may demand firms restrategising their internal factors and level of compliance towards environmental sustainability in project delivery. Using a cross-sectional data collection method , 185 respondents from Malaysian G7 construction firms participated in this research. We utilised partial least squares path modelling for data analysis. Our findings established strong empirical evidence for the hypothesised positive effects of company culture, managerial attitudes and coercive pressure on environmental sustainability performance. However, social responsibility is revealed to have no effect on environmental sustainability performance. This is not unconnected with the fact that most Malaysian firms incur more social responsibility expenditure in the social sector than the environment. Our findings also established that coercive pressure is a positive mediator and a catalyst that plays a complementary role between managerial attitudes, company culture and social responsibility, and environmental sustainability performance. Policy implications and future study's directions are equally discussed.